The American Academic Profession at Risk - Finkelstein, Martin J. (International Higher Education, 2017)
The Faculty Factor (Johns Hopkins University Press, 2016) creatively mines fresh—and heretofore unavailable—data sources to follow the fortunes of the American faculty through the lingering Great Global Recession of 2008. Building on The American Faculty (Johns Hopkins, 2006), Finkelstein and Schuster, now joined by Valerie Martin Conley, document the emergence of a “new” model of academic work and careers in the United States built on an increasingly contingent, stratified academic workforce; the unbundling of the traditionally integrated role into specialist teaching, research and administrative roles, and the progressive yielding of faculty authority on campus, even in academic matters, to a growing core of full-time professional administrators. This volume includes two chapters that explicitly place the U.S. faculty in international perspective.